Grammaticalization and Lexicalization: A Discourse Analysis of Modality Expressed in English and Romblomanon in Classroom Interaction and Conversation - Mindoro, Orlando (Romblon State University Research Journal, 2023)
The Romblomanon language profoundly influenced the learning process of acquiring English as a second language. In this study, the researcher focused on how Romblomanon learners expressed modality in English, which can be defined by grammaticalization (mood, tense, aspect, among others) and lexicalization (modal verbs, modal adverbs, modal adjectives, among others). Romblomanon modality can also be expressed in three universal semantic roles: agent, theme, and location. This study used the qualitative discourse analysis method using the descriptive and contrastive approach to identify English and Romblomanon modals expressed in actual classroom interaction and conversation of Romblomanon students. The recorded conversation and interaction from the two subjects of the students majoring in English enrolled at Romblon State University-Romblon Campus were transcribed and analyzed based on their epistemic and deontic meanings. Results showed that many Romblomanon English learners constructed their statement in Romblomanon and translated itno literally to English statements. It was concluded that the Romblomanon English learners are deeply influenced by their native tongue, resulting in the misuse of modality.